Internal Pudendal Artery Perforator Flap Reconstruction After Post-Radical Vulvectomy: A Case Report - Anak Agung Ayu Anggreni; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya (Jurnal llmu Bedah Indonesia, 2021)
Introduction. Reconstruction of vulvar defects following radical vulvectomy can be challenging. It is related to the functional and aesthetic aspects of the woman's body important part. In addition, the nature of the vulvar region also affects wound healing. This case report aims to share our experience in managing vulvar defects using the internal pudendal artery perforator (IPAP) flap. Case Description. We present a thirty-year-old woman with carcinoma of the vulva stage IB (tumor size 8×3 cm). The gynecologic oncologist performed radical vulvectomy and bilateral inguinal lymph nodes removal using separate groin incisions. Those procedures result in a 16×8 cm vulvar defect. We reconstructed the bilateral defects using right IPAP flap-type I-1 (propeller flap), left IPAP flap-type II (V-Y advancement flap), and a vaginoplasty in the lithotomy position. The flaps were designed based on Doppler signals. The vulvar defect was successfully recovered, and no complications were observed, including cellulitis, wound dehiscence, and flap necrosis of the reconstructed and donor sites. Conclusion. IPAP flap is a well-vascularized flap suitable for areas with the inherent risk of delayed wound healing, such as the vulvar region. IPAP flap might benefit vulvar reconstruction regarding the shape, volume, and function restoration.